2018
DOI: 10.3758/s13414-018-1613-9
|View full text |Cite|
|
Sign up to set email alerts
|

Alertness and cognitive control: Is there a spatial attention constraint?

Abstract: Congruency effects in arrow flanker tasks are often larger when subjects are more alert, suggesting an unusual connection between alertness and cognitive control. Theoretical accounts of the alerting-congruency interaction differ with respect to whether and how spatial attention is involved. In the present study, the author conducted eight experiments to determine whether there is a spatial attention constraint linking alertness to cognitive control. Alertness was manipulated in color-word Stroop tasks involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…Previous studies showed that error rates resort to individuals’ inhibitory control 79 81 . For instance, people deficient in inhibitory control had difficulty waiting to press a button, being inclined to make more errors 82 . In the Go/No-go test, participants with poor inhibition had difficulty in suppressing an impulse to respond to a ‘No-go’ signal, whereupon they made substantial errors and as a result had trouble with learning 79 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that error rates resort to individuals’ inhibitory control 79 81 . For instance, people deficient in inhibitory control had difficulty waiting to press a button, being inclined to make more errors 82 . In the Go/No-go test, participants with poor inhibition had difficulty in suppressing an impulse to respond to a ‘No-go’ signal, whereupon they made substantial errors and as a result had trouble with learning 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Set-shifting, also known as cognitive flexibility or mental flexibility, designates changing perspectives by virtue of accommodating new requirements or rules and overcoming inertial behavior 82 . Specifically in the motor domain, it is important to be flexible for learners to shift stimulus–response mappings correctly for a given trial during the course of learning 26 , 89 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, this overarching benefit of 1 Auditory signals (e.g., tones) have also been used as alerting cues in variants of the ANT and in related paradigms (e.g., Callejas, Lupiáñez, & Tudela, 2004;Fischer, Plessow, & Kiesel, 2010Seibold, 2018;Weinbach & Henik, 2012). However, as noted by Schneider (2019a), the combination of auditory alerting cues and visual stimuli confounds the alerting manipulation with modality switching (i.e., attention switches between auditory and visual modalities during alert trials, but not during no-alert trials). Modality switching is known to affect task performance (e.g., Lukas, Philipp, & Koch, 2010;Quinlan & Hill, 1999), suggesting that the modality of the alerting cues might be important to consider in decisions about experiment design.…”
mentioning
confidence: 99%